Market Intelligence Briefs – a new publication series to inform crop-breeding decisions - Donovan, Jason; Rutsaert, Peter (CGIAR, 2023)
Traditionally, researchers from CGIAR, NARES and universities who have sought to inform crop breeding and seed systems programming have done so by publishing their work in reputable international peer-reviewed journals. However, the process can be slow, potentially requiring multiple revisions over years. The practical nature of market intelligence research can limit its relevance for journal editors who are looking to push theoretical debates forward. Thus, for Market Intelligence to deliver on its promise, new ways of communicating will be essential. In looking to address these limitations, work package 1 has led the design and implementation of a new publication series called Market Intelligence Briefs (MIB).